Imaging abnormalities of the acromioclavicular joint and subacromial space are common in asymptomatic shoulders: a systematic review - Thomas Ibounig; Lasse Rämö; Romi Haas; Mark Jones; Teppo L. N. Järvinen; Simo Taimela; Sean Docking; Sharon Sanders; Rachelle Buchbinder (Journal of Orthopaedic Surgery and Research)
Abstract Objectives To determine the prevalence of acromioclavicular (AC) joint and subacromial space imaging abnormalities in asymptomatic adults, with a secondary objective of comparing findings between asymptomatic and symptomatic shoulders within the same study populations. Methods We conducted a systematic review of studies examining shoulder imaging abnormalities detected by X-ray, ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) in asymptomatic adults (PROSPERO registration CRD42018090041). This report focuses on AC joint and subacromial space abnormalities. Databases searched included Ovid MEDLINE, Embase, CINAHL and Web of Science from inception to June 2023. Our primary analysis used data from population-based studies, and risk of bias and certainty of evidence were evaluated with tools for prognostic studies. Results Thirty-one studies (4 X-ray, 11 US, 15 MRI, 1 both X-ray and MRI) provided useable prevalence data. One study was population-based (20 shoulders), 16 included miscellaneous study populations (2436 shoulders) and 14 focused on athletes (708 shoulders). The certainty of evidence was very low mainly due to high risk of bias, imprecision, and indirectness across studies. Clinical diversity precluded pooling. Population-based prevalence of acromioclavicular osteoarthritis (AC OA) ranged from 85% on MRI to 95% on X-ray. In other study populations, AC OA prevalence in asymptomatic shoulders varied from 6 to 47% on X-ray, 1 to 65% on US, and 0 to 82% on MRI. Among eight studies that included both asymptomatic and symptomatic shoulders, AC OA prevalence ranged from 13 to 95% in asymptomatic shoulders and from 20 to 100% in symptomatic shoulders. Conclusion The prevalence of AC joint and subacromial space abnormalities in asymptomatic shoulders is highly variable, and often comparable to that in symptomatic shoulders. Due to the low certainty of evidence and significant variation among study populations, further research is needed to clarify these prevalence estimates and to guide evidence-based management of shoulder abnormalities.